Gender Bias in the Evaluation of Teaching Materials - Özgümüs, Asri; Rau, Holger A.; Trautmann, Stefan T.; König-Kersting, Christian (Frontiers in Psychology, 2020)
Gender differences in university teaching evaluations are well established, showing less favorable assessments of female instructors. It has also been shown that these differences cannot be linked to differences in students’ course performance, which would justify differences in evaluations. The less favorable assessments are thus either due to differences in aspects that do not affect student performance, but do affect their class experience (e.g., likability of voice tone), or due to evaluation biases unrelated to any actual differences in class experience. We find support for the latter mechanism when any differences between instructors are excluded by having respondents judge identical teaching materials prepared by either a male or a female instructor. In two studies we find that female instructors receive worse ratings than male instructors from male respondents. In one study we also find that female instructors receive higher ratings from female raters. Gender bias vanishes for non-academic subjects in our data.